Contextualizing Anti-Migrant Sentiment: A Comparative Ethnography of Lesvos and Samos, Greece - Kouros, Theodoros (My University, 2025)
This article offers a comparative ethnographic analysis of anti-migrant mobilizations on the Greek Aegean islands of Lesvos and Samos between 2018 and 2022. While both islands experienced intensified border securitization, refugee containment, and NGO activity following the EU–Turkey Deal, their local responses diverged markedly. Lesvos became a site of organized and visible vigilante violence, in contrast to Samos, where little comparable turmoil occurred, and where unrest was characterized by informal exclusion and ambient hostility. Drawing on ten months of ethnographic fieldwork, this study argues that migration pressures alone cannot explain these divergent patterns. Instead, they reflect the interplay of geography, community scale, far-right mobilization, and state complicity. Vigilantism, the paper suggests, should be understood not as a rupture in the rule of law, but as part of a broader moral and spatial infrastructure of border governance, one that operates through both action and silence. By tracing how proximity, reputation, and visibility shape the moral economies of violence and restraint, the article contributes to debates on migration, vigilantism, and the affective politics of European borderlands.
Keywords: infrastructures; borders; Refugees; Aegean; vigilantism; ar-right